EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN VIDEOSCRIBE UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR DESAIN GRAFIS DI SMK NEGERI 5 SURAKARTA - Luluk Monitasari; Endar Suprih Wihidayat; Yusfia Hafid Aristyagama (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
Based on the results of observations at SMK N 5 Surakarta in the Basic Graphic Design subject, it shows that student motivation and learning outcomes are still low. Based on the previous learning results, it was found that 18.1% of students scored above the minimum completeness criteria (KKM ≥ 75) while the level of learning motivation of students showed that learning motivation was still low and less enthusiastic in learning. Based on these problems, an effort is needed to increase motivation and learning outcomes using Videoscribe learning media in learning. The selection of videoscribe media is because it is able to present visuals that come from a combination of text, sound, images that are combined into animation according to the needs in learning basic graphic design related to visuals. This study used a quasi experimental design with a nonequivalent control group design. Questionnaires were used to measure motivation, while student learning outcomes were measured using tests. The results of the research hypothesis test showed an increase in learning motivation in the experimental class with Ngain of 0.46 in the moderate category. While the learning outcomes in the experimental class also increased higher than the control class with Ngain of 0.34 in the moderate category.